SYSTEMATICS LITERATURE REVIEW : TREN PENELITIAN TENTANG PENGARUH MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DI INDONESIA - Rofifah, Jihan; Meiliasari, Meiliasari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This study is to do a literature review about the impact of learning media on enhancing the comprehension of mathematical ideas at the elementary, junior high, and high school levels. This study employs the Systematic Literature Review (SLR) methodology. Data collection was conducted by identifying and evaluating reference searches obtained from Publish or Perish (PoP) and Google Scholar. The sample comprised journals indexed by Sinta 2-4 from 2020 to 2024. Subsequently, 20 articles were acquired that corresponded to the keywords related to learning media aimed at enhancing students' comprehension of mathematical concepts, and 20 articles were picked in accordance with the study criteria established. The literature review analysis concludes that the application of digital learning media has increasingly influenced students' understanding of mathematical concepts, particularly in geometry, over the past five years. Simultaneously, studies concerning the comprehension of mathematical ideas are extensively published in Sinta 3 indexed journals under the R&D research category. Researchers conducted a greater volume of studies at the junior high school level, producing 8 publications and trends in 2022.